2017
DOI: 10.1002/pi.5425
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cardo containing asymmetric poly(ether-naphthalimide-phthalimide)s

Abstract: A series of cardo based asymmetric polyimides containing bulky rigid naphthalimide and phthalimide groups were prepared from asymmetric monomer bishaloimide and bisphenols by solution polycondensation. Bishalo(naphthalimide-phthalimide) monomers containing different terminal leaving groups (Cl, F, NO 2 ) were synthesized, and the reactivity difference of these monomers was compared for the successful synthesis of polyimides. The inherent viscosities of the polyimides were in the range 0.51 − 0.60 dL g −1 in N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The ANS monomers with bulky side group are more accessible than diamine or dianhydride counterparts. Therefore, in the last two decades, ANS polymerization has been mainly used for preparing organo-soluble lightcolored (Figure 6B) [64][65][66][67][68][69][70][71][72] and colorless PIs (Figure 6C). 65,66,68,71 Ether and isopropyl linkages as well as bulky side groups (e.g., cardo unit) are common for improving solubility in organic solvents and reduce colors.…”
Section: Aromatic Nucleophilic Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANS monomers with bulky side group are more accessible than diamine or dianhydride counterparts. Therefore, in the last two decades, ANS polymerization has been mainly used for preparing organo-soluble lightcolored (Figure 6B) [64][65][66][67][68][69][70][71][72] and colorless PIs (Figure 6C). 65,66,68,71 Ether and isopropyl linkages as well as bulky side groups (e.g., cardo unit) are common for improving solubility in organic solvents and reduce colors.…”
Section: Aromatic Nucleophilic Substitutionmentioning
confidence: 99%
“…(B) Examples of organosoluble PIs containing ether backbone linkages. Among these, most have been prepared via NAS (B1, B2, B5‐B7), and several contain varying cardo structures (B5–B7) 64,65,68,72 . (C) examples of organosoluble, colorless PIs, most of which are prepared via NAS.…”
Section: Syntheses Of Polyimidesmentioning
confidence: 99%
“…On the other hand, the glass transition temperatures ( T g ) of resulting PIs may be decreased due to the introduction of such flexible linkages using diphenols as monomers . Fortunately, the introduction of a bulky substituent, such as a cardo group, has been demonstrated to improve the thermal properties and solubility of PIs at the same time because cardo polymers with phenolphthalein bulky side moieties could retain the rigidity of the polymer backbone and restrict the close packing of the polymer chains . More importantly, the transparency of cardo PIs can be enhanced due to the extension of the distance between the macromolecular chains, effectively suppressing conjugation and decreasing charge transfer complex formation …”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Fortunately, the introduction of a bulky substituent, such as a cardo group, has been demonstrated to improve the thermal properties and solubility of PIs at the same time because cardo polymers with phenolphthalein bulky side moieties could retain the rigidity of the polymer backbone and restrict the close packing of the polymer chains. [34][35][36][37][38][39] More importantly, the transparency of cardo PIs can be enhanced due to the extension of the distance between the macromolecular chains, effectively suppressing conjugation and decreasing charge transfer complex formation. 29,30 In the study reported here, considering that the incorporation of cyclohexane and cardo groups would endow PIs with high transmittance and good solubility without sacrificing thermal stability, two novel series of transparent cardo PIs derived from CHDA were synthesized using cardo phthalein diphenols and bis(fluorophthalimide)s as monomers via aromatic nucleophilic substitution polymerization.…”
Section: Introductionmentioning
confidence: 99%